The relationships between inflammatory biomarkers, plaque characteristics, and macrophage clusters in coronary plaque: a quantitative assessment of macrophages based on optical coherence tomography - Liu, Chunwei; Yang, Fan; Hu, Yuecheng; Wang, Le; Li, Ximing; Cong, Hongliang; Zhang, Jingxia (Frontiers in Cardiovascular Medicine, 2025)
BackgroundQuantitative assessment of macrophage accumulation is appealing in evaluating plaque inflammation. In optical coherence tomography (OCT) imaging, local macrophage clusters may be a feasible marker for macrophage quantification.Methods404 patients presenting with acute coronary syndrome who underwent OCT evaluation were included. This study aims to assess the relationships between systemic inflammatory biomarkers [including monocytes, high-density lipoprotein cholesterol (HDL-C), and monocyte-to-HDL ratio (MHR)], plaque characteristics, and local macrophage clusters in coronary plaque.ResultsMacrophage clusters were present in 218 patients, with a median arc value of 72° (50°–163°). Patients with macrophage clusters showed markedly higher levels of inflammatory biomarkers and plaque vulnerability. Multivariate logistic regression analysis demonstrated that MHR, lipid index, and microchannel were independently associated with the presence of macrophage clusters. The DeLong test showed the area under the curve of the above three combined indicators was significantly larger than that of single indicators (0.774 vs. 0.692, 0.665, 0.624, respectively, p < 0.001). The macrophage cluster arc correlated positively with MHR and lipid index (r = 0.219, p = 0.001; and r = 0.229, p = 0.001, respectively). More superficial macrophage infiltration, thin cap fibroatheromas, plaque rupture, and thinner fibrous cap thickness were observed in the large macrophage cluster group (>72°) compared to the small macrophage cluster group (50°–72°). The macrophage cluster arc in the low MHR + lipid index group was significantly lower than that in the high MHR + lipid index group (68° ± 17° vs. 84° ± 26°, p = 0.001). Multiple linear regression analysis demonstrated that MHR, age, and lipid index were independently associated with macrophage cluster arc. In subgroup analysis stratified by clinical presentation and high-sensitivity C-reactive protein level, higher MHR and lipid index levels were observed in large macrophage clusters than in the non-macrophage cluster group, irrespective of the inflammation background.ConclusionsThe macrophage cluster was a valuable index for quantifying local plaque inflammation. MHR, lipid index, and microchannel were independently associated with macrophage clusters. Large macrophage clusters were independently associated with high MHR and high lipid plaque burden.